Relevansi Hadis Dalam Film Animasi “Belajar Jujur” Di Kanal Youtube Nussa & Rara (Kajian Ma‘ānī al-Ḥadīth) - Nur Hali (LPPM IAI Hasanuddin Pare-Kediri, 2025)
Abstract Maʿānī al-Ḥadīth is a branch of ḥadīth studies that seeks to understand the meaning, values, and moral messages of the Prophet Muhammad’s sayings, both textually and contextually. This approach is essential for interpreting ḥadīth values within contemporary media, including animated films. The Nussa episode “Belajar Jujur” (“Learning to Be Honest”) serves as a medium of da‘wah that conveys Islamic moral messages in an engaging and easily understandable way for children. This study aims to analyze the values of honesty depicted in the Nussa episode “Learning to Be Honest” through the perspective of Maʿānī al-Ḥadīth. The research method used is qualitative with a library research approach. Data were obtained from the film, ḥadīths related to ṣidq (honesty), and relevant literature. The analysis was conducted using a descriptive-analytical method by applying Maʿānī al-Ḥadīth theory to reveal the relevance between the meaning of the ḥadīths and the film’s message. The results indicate that the film portrays honesty through the protagonist’s willingness to admit mistakes and avoid lying. These values align with the Prophet’s ḥadīths which emphasize that honesty leads to goodness and ultimately to Paradise. In conclusion, Nussa functions as an effective educational da‘wah medium for internalizing ḥadīth values regarding honesty. Keywords: Maʿānī al-Ḥadīth, Honesty, Relevance, Nussa film.